Harlem Renaissance - Huggins, Nathan Irvin, 1927-1989 (Oxford University Press, 2007)
A finalist for the 1972 National Book Award, hailed by The New York Times Book Review as ""brilliant"" and ""provocative, "" Nathan Huggins' Harlem Renaissance was a milestone in the study of African-American life and culture. Now this classic history is being reissued, with a new foreword by acclaimed biographer Arnold Rampersad. As Rampersad notes, ""Harlem Renaissance remains an indispensable guide to the facts and features, the puzzles and mysteries, of one of the most provocative episodes in African-American and American history."" Indeed, Huggins offers a brilliant account of the creative